Public satisfaction with the police in domestic violence cases: The importance of arrest, expectations, and involuntary contact - Wilson, Steve (American journal of criminal justice, 2004)
This study examines the importance of victims’ expectations of the police, the decision to arrest, and voluntary contact on satisfaction ratings of the police in domestic violence cases. Based on results from past research and modern police policy, several hypotheses are tested including: fulfilled expectations, offender arrests, and voluntary contacts resulting in positive satisfaction ratings of the police. To investigate these predictions further, the present study utilizes data from a national study on violence against women in the United States. Logistic regression analyses indicate that fulfilled expectations and the arrest decision are important to positive satisfaction ratings. Findings also indicate that involuntary, not voluntary, contact with the police leads to higher satisfaction ratings.